Biodiesel and poly‐unsaturated fatty acids production from algae and crop plants – a rapid and comprehensive workflow for lipid analysis. Issue 10 (11th August 2016) - Furuhashi, Takeshi; Nakamura, Takemichi; Fragner, Lena; Roustan, Valentin; Schön, Verena; Weckwerth, Wolfram
Abstract: Fatty acid methyl ester analysis (FAME) by gas chromatography coupled to mass spectrometry (GC‐MS) is a widely used technique in biodiesel/bioproduct (e.g. poly‐unsaturated fatty acids, PUFA) research but typically does not allow distinguishing between bound and free fatty acids. To understand and optimize biosynthetic pathways, however, the origin of the fatty acid is an important information. Furthermore the annotation of PUFAs is compromised in classical GC‐EI‐MS because the precursor molecular ion is missing. In the present protocol an alkaline methyl esterification step with TMS derivatization enabling the simultaneous analysis of bound and free fatty acids but also further lipids such as sterols in one GC‐MS chromatogram is combined. This protocol is applied to different lipid extracts from single cell algae to higher plants: Chlorella vulgaris, Chlamydomonas reinhardtii, Coffea arabica, Pisum sativum and Cuscuta japonica . Further, field ionization (GC‐FI‐MS) is introduced for a better annotation of fatty acids and exact determination of the number of double bonds in PUFAs. The proposed workflow provides a convenient strategy to analyze algae and other plant crop systems with respect to their capacity for third generation biodiesel and high‐quality bioproducts for nutrition such as PUFAs. Abstract : CO2 ‐neutral food, feed, fiber and biofuel production will be tremendeously important in the next decades of global climate change and the transition from fossil fuels to renewable energy resources. Lipid production with plants and algae is an essential part of the food chain and gains more and more importance as an alternative biofuel resource. A bioanalytical workflow for the rapid and comprehensive characterisation of lipid production in algae and other plant crop systems with respect to their capacity for third generation biodiesel and high‐quality bioproducts for nutrition such as PUFA's is developed.